Epigenetics of Cellular Reprogramming - Krishnakumar, Raga (Curr Opin Genet Dev, 2013)
Cells are constantly changing their state of equilibrium in response to internal and external stimuli. These changes in cell identity are driven by highly coordinated modulation of gene expression. This coordinated regulation is achieved in large part due to changes in the structure and composition of the chromatin, driven by epigenetic modulators. Recent discoveries in cellular and genomic reprogramming have highlighted the importance of chromatin modifications to reach and uphold the fidelity of target cell states. In this review, we focus on the latest work addressing the mechanisms surrounding the epigenetic regulation of various types of reprogramming, including somatic cell nuclear transfer (SCNT), cell fusion and transcription factor- and microRNA-induced pluripotency. The studies covered herein showcase the interplay between these epigenetic pathways, and highlight the importance of furthering our understanding of these connections to form a clearer picture of the mechanisms underlying stable cell fate transitions.